Analysis on Teaching and Learning Conceptions of Physical Education Teacher Candidates by Different Variables - Mustafa Enes Işıkgöz (ümit doğan üstün, 2020)
This study, in which the teaching and learning conceptions of physical education teacher candidates were examined, was designed in a descriptive scanning model. The study group of the research consists of a total of 752 students, 312 males and 440 females who study in the Physical Education and Sports Teaching program of the Schools of Physical Education and Sports. In the research, an online questionnaire form created by using google docs infrastructure was used as data collection tool. The link of the survey form was shared with the relevant student and faculty member groups, and the survey was ensured to be filled on a voluntary basis. "Personal Information Form" and "Teaching and Learning Conceptions Scale" were used in the data collection tool. The scale is composed of a total of 30 items and two sub-dimensions namely "Constructivist Conception" and "Traditional Conception". "Constructivist Conception Dimensions" consists of 12 items and "Traditional Conception Dimensions" consists of 18 items. In the analysis of the data, Kolmogorov Smirnov test was first used for normality test, and it was determined following the test that data did not show normal distribution. In this context, non-parametric tests Mann-Whitney U and Kruskall-Wallis H tests were used in the analyzes, and Bonferroni correction was made to control Type I error in the analyzes. After Kruskal-Wallis H Test, Mann-Whitney U Test was used for post-hoc test among groups with significant difference. It was concluded in the study that the physical education teacher candidates mostly adopted the constructivist teaching and learning approach although they agreed with the traditional teaching and learning approach but at a low level. It was determined that the teaching and learning conceptions of physical education teacher candidates did not change significantly by the gender variable, but significantly changed according to the variables of national sportsmanship, scholarship, grade level and place of residence. Students who are national athletes and receive scholarships have a higher perception of traditional teaching and learning. It has been determined that as the class level increases, the physical education teacher candidates adopt the constructivist teaching and learning conception, and the students living in the dormitories adopt the traditional teaching and learning conception more.